CUSTOMER DUE DILIGENCE DALAM MENCEGAH TINDAK PIDANA PENCUCIAN UANG MELALUI LEMBAGA PERBANKAN - Eko Prakoso Johannes (Law Review, 2019)
The ease of conducting a banking transactions makes it vulnerable to become a vehicle for money laundering. The purpose of this article is to understand the existence and procedure of Customer Due Diligence (CDD) principles in banking to prevend money laundering that is based on the Financial Services Authority Regulation Number 12/POJK.01/2017. The research method used is normative juridical legal research using a statute approach. The result of the study show that the Bank as a Financial Services Provider is required to implement a Customer Due Diligence (CDD) principle to ensure that every banking transactions are in accordance with the profile, characteristics and/or transaction patterns of prospective customers, customers or walk in customers (WIC). Banks are required to report suspicious banking transactions to Financial Transaction Reports and Analysis Center (PPATK).